2022
DOI: 10.1186/s12920-022-01387-6
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of DNA methylation and expression of genes related to thyroid hormone metabolism in colon epithelium of obese patients

Abstract: Background Colorectal cancer is common among obese individuals. The purpose of the current study was to determine changes in DNA methylation status and mRNA expression of thyroid hormone receptor beta (THRB), as a tumor suppressor, and thyroid hormone inactivating enzyme, type 3 deiodinase (DIO3) genes, in human epithelial colon tissues of healthy obese individuals. Methods Colon biopsies were analyzed by methylation sensitive-high resolution melt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Thyroid hormone receptors are coded by two genes: alfa and beta. The epigenetic regulation of THRB has previously been shown to be involved in many human phenotypes such as cancer, obesity, and aging (Joseph et al 2007; Ling et al 2010; Kim et al 2013; Pawlik-Pachucka et al 2018; Shimi et al 2022), and affected by exposures to e.g. thyroid hormones and environmental toxins in mice (Cho et al 2021; Laufer et al 2022), and thus we were interested in investigating if that is the case also in the context of avian maternal hormones, and chose THRB for the methylation analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Thyroid hormone receptors are coded by two genes: alfa and beta. The epigenetic regulation of THRB has previously been shown to be involved in many human phenotypes such as cancer, obesity, and aging (Joseph et al 2007; Ling et al 2010; Kim et al 2013; Pawlik-Pachucka et al 2018; Shimi et al 2022), and affected by exposures to e.g. thyroid hormones and environmental toxins in mice (Cho et al 2021; Laufer et al 2022), and thus we were interested in investigating if that is the case also in the context of avian maternal hormones, and chose THRB for the methylation analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Thyroid hormone receptors are coded by two genes: alfa and beta. The epigenetic regulation of THRB has previously been shown to be involved in many human phenotypes such as cancer, obesity, and aging (Joseph et al, 2007; Kim et al, 2013; Ling et al, 2010; Pawlik‐Pachucka et al, 2018; Shimi et al, 2022), and affected by exposures to, for example, thyroid hormones and environmental toxins in mice (Cho et al, 2021; Laufer et al, 2022), and thus we were interested in investigating if that is the case also in the context of avian maternal hormones, and chose THRB for the methylation analyses.…”
Section: Methodsmentioning
confidence: 99%
“…However, the underlying mechanism of gut microbiome and metabolites on obesity remains unclear. Changes in colonic transcriptome was observed in HFD-induced obesity [9] and human [10], suggesting that gut microbiota and metabolites may affect colonic gene expression. Qin et al [11] suggested that the gut microbiome stimulates a reprogramming of the enhancer landscape in the colon, with downstream effects on transcription factors under specific dietary exposures.…”
mentioning
confidence: 99%
“…However, the underlying mechanism of gut microbiome and metabolites on obesity remains unclear. Changes in colonic transcriptome was observed in HFD‐induced obesity [ 9 ] and human [ 10 ], suggesting that gut microbiota and metabolites may affect colonic gene expression. Qin et al .…”
mentioning
confidence: 99%